Analisis Kojoin Full Profile Dalam Pemilihan Kerudung untuk Mahasiswi Departemen Matematika Universitas Negeri Padang - Pertiwi, Monica; Murni, Dewi (UNIVERSITAS NEGERI PADANG, 2023)
The veil is a kind of scarf that covers most of the top of a woman's head. The veiled order is an obligation and obedience to Allah and His Messenger. Now there are many types of headscarves such as rectangular or pashmina headscarves, making female students have to be selective in choosing a headscarf according to their needs but still follow the existing trends. This research aims to the preferred combination of UNP Mathematics Department students in choosing a headscarf. This study showed that the combination that students liked the most was pashmina headscarves, ceruty, plain, price ≤Rp. 35,000. With the highest level utility value at the price attribute ≤Rp.35,000 with the highest relative importance value of 58.10%.